Ikarie XB 1 - Lem, Stanisław 1921-2006; Liška, Zdeněk 1922-1983 (Second Run, 2019)
"Polák’s pioneering and much-imitated feature Ikarie XB 1 is one of the cornerstones of contemporary science fiction cinema. It predates Star Trek and Kubrick’s 2001: A Space Odyssey and was clearly a pronounced influence on both - and on countless other sci-fi films and TV shows that followed. Adapted from Stanisław Lem's novel The Magellanic Cloud, the film is set in 2163 and follows a mission deep into space in search of alien life. During their perilous journey the crew confront the effects of a malignant dark star, the destructive legacy of the 20th century and, ultimately, the limits of their own sanity. With outstanding design and cinematography, and a superb score by Zdeněk Liška, Ikarie XB 1 is imbued with a seriousness, intelligence and attention to detail rarely seen in science-fiction cinema of the period." [secondrundvd.com]
Original: Tscheoslowakei 1963
Special features: presented from an HD transfer of the new 4K restoration by the Czech National Film Archive ; a filmed appreciation by author and critic Kim Newman ; The most ordinary of occupations (1963) - a short film by Josef Koran on science and mathematics ; Voyage to the end of the universe - opening credits and end-sequence from the alternative, dubbed US version ; 20-page booklet featuring a substantial essay by writer and film Historian Michael Brooke ; trailers ; photo gallery
Bildformat 2.35:1
Keywords: Film; Blu-Ray-Disc